The Environmental crisis--opposing viewpoints - Bernards, Neal, 1963- (Opposing viewpoints series (Unnumbered), 1991)
Presents opposing views on questions of environmental protection and damage resulting from air and water pollution, toxic wastes, pesticides, and the ever-growing tide of refuse.